Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.2466/pr0.1990.67.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Meaning through the Lifespan

Abstract: 185 men and women representing five developmental ages ranging from younger to older adulthood (17 to 96 yr) completed several measures to assess the amount and origins of most meaningful events in a person's life. As assessed by a modification of the Purpose-in-Life Test, the amount of purpose did not vary per se with age or sex. Similarly, the sources of meaning did not alter across time or sex. Themes of involvement emerged as the salient sources of meaning and included love, work, births of children, indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 19 publications
4
26
0
2
Order By: Relevance
“…Psychologists' responses on the MILQ indicated that intimate relationships, family, and friendships brought the greatest meaning to their lives. These results are consistent with other studies that have consistently identified relationships with people as the most frequent source of meaning across the lifespan (Baum & Stewart, 1990;Debats, 1999;DeVogler & Ebersole, 1981;O'Connor & Chamberlain, 1996;Taylor & Ebersole, 1993;Yalom, 1980). These results are also consistent with Kaufman's (1986) assertion that most people express four to six main themes in their life stories.…”
Section: Psychologists' Personal Meaning In Lifesupporting
confidence: 94%
“…Psychologists' responses on the MILQ indicated that intimate relationships, family, and friendships brought the greatest meaning to their lives. These results are consistent with other studies that have consistently identified relationships with people as the most frequent source of meaning across the lifespan (Baum & Stewart, 1990;Debats, 1999;DeVogler & Ebersole, 1981;O'Connor & Chamberlain, 1996;Taylor & Ebersole, 1993;Yalom, 1980). These results are also consistent with Kaufman's (1986) assertion that most people express four to six main themes in their life stories.…”
Section: Psychologists' Personal Meaning In Lifesupporting
confidence: 94%
“…Despite lacking standards for the content analysis of autobiographical data, a global review of different studies shows some similarity in type of reported life events between men and women of different ages. For instance, Baum and Stewart (1990), as well as deVries and Watt (1996), found that women generally are more focused on school issues, romance, and childbirth, whereas workrelated events are more important for men. Younger adults mention more school-related events, friendship, and sexuality; middle-aged adults mention more childbirth and growth activities; and older respondents mention war, retirement, and health as being more important.…”
Section: E Content Of Livesmentioning
confidence: 96%
“…The third research propositions therefore states: (Battista & Almond, 1973). Although some studies found correlations between meaning in life and age (Baum & Stewart, 1990;Debats & Drost, 1995), empirical research results on the relationship of the degree of meaning with age are contradicting. In fact, most studies failed to find statistically significant relationships between meaning in life and biographical variables such as age, sex, qualifications, or culture (e.g., Debats et al, 1993;Debats, 1999;De Vogler-Ebersole & Ebersole, 1985).…”
Section: Work Centralitymentioning
confidence: 98%
“…In fact, research in sociology on the functions of work identified meaning as one of seven main rea sons why people work (Johada, 1982;Gill, 1999). Other studies found work to be a frequent source of meaning in life (Baum, & Stewart, 1990;Debats, 1999). Engagement in meaningful work is a central tenet of occupational therapy (Strong, 1998).…”
Section: Work Centralitymentioning
confidence: 99%
See 1 more Smart Citation